Implementasi Kurikulum Merdeka Belajar di Daerah Kepulauan: Studi Kasus di SMA Negeri 1 Kepulauan Sula - Bakri Titdoy; Decky W. Kamagi; Jantje Ngangi (International Forum of Researchers and Lecturers, 2025)
This study aims to evaluate the implementation of the Independent Learning Curriculum at SMA Negeri 1 Sula Islands, an educational institution located in the archipelago with its own geographical characteristics and challenges. The focus of this study is to assess the effectiveness of curriculum implementation in shaping a flexible, participatory, and contextual learning experience. Using a descriptive quantitative approach, data was collected through questionnaires of school principals, vice principals for curriculum and student affairs, and grade XI science and social studies students. The results of the study showed that all respondents from school management gave an assessment of the